ANALISIS PENERAPAN NILAI BUDAYA SAFETY MELALUI BATURAJA RISK CONTAINMENT KARYAWAN PT SEMEN BATURAJA (PERSERO) Tbk - Meriadi Meriadi; Fakhry Zamzam; Luis Marnisah (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
Research objectives specifically to know the results of the analysis of the implementation of the value of cultural safety through the Baturaja Risk Containment employee Level Junior Manager and Specialist at PT. Semen Baturaja Site Baturaja. The method of research that is used is qualitative descriptive by emphasizing analysis of data obtained in the field. Data collection in the field using observation and interview techniques. Data sources and information obtained from informant that is an employee of the Junior manager and specialist and also key informant from the officials at the Vice president, Senior Manager and Manager who experienced more than six years in the field. The results of the study stated that before the program BRC employees did not care and do not understand the importance of occupational safety. After the implementation of BRC program there is a change in safety culture of employees with increased awareness of 64%, increased adherence to safety rules by 14% and increased understanding of safety culture by 22%. Factors supporting the creation of cultural safety include 60% of consciousness, 25% of fear due to sanctions and 15% pressure from superiors. The positive impact of the BRC program makes employees more concerned about the culture of safety. With the commitment and maximum support from the cement Baturaja, the value of cultural Safety through BRC program for employees of Semen Baturaja in Junior Manager and Specialist disite Baturaja can not only be realized well but also provide a positive image for investors and the public.